2022
DOI: 10.3389/fpsyg.2022.794279
|View full text |Cite
|
Sign up to set email alerts
|

Working Online During COVID-19: Accounts of First Year Students Experiences and Well-Being

Abstract: The sudden move to online learning due to the COVID-19 pandemic has created an influx of epistemological, psycho-social, emotional and financial challenges for first year students. Lecturers and academics had to find creative and sustainable ways of ensuring that all students were epistemologically included. New policies and practices were introduced rapidly at universities to facilitate the unavoidable move to online learning. As initial teacher educators at a public University in South Africa we noted that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Now, as higher education zips towards automation under what may be described as the new “technocratic imperative”, we see the emergence of online learning platforms to further improve the efficiency of instruction (Cavus and Zabadi, 2014). Online learning, or e-learning offers the benefit of targeted course offerings, location flexibility, time flexibility, immediate feedback and personalised learning to name a few (Moosa and Bekker, 2022). MOOCs, a flagship of e-learning, and have become an important ingredient of discourse in tertiary education (Liapis et al , 2022; Oh et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Now, as higher education zips towards automation under what may be described as the new “technocratic imperative”, we see the emergence of online learning platforms to further improve the efficiency of instruction (Cavus and Zabadi, 2014). Online learning, or e-learning offers the benefit of targeted course offerings, location flexibility, time flexibility, immediate feedback and personalised learning to name a few (Moosa and Bekker, 2022). MOOCs, a flagship of e-learning, and have become an important ingredient of discourse in tertiary education (Liapis et al , 2022; Oh et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a consequence of COVID-19, first-year students have had to navigate major life transitions together with the unanticipated move to online teaching and learning (Combrink & Oosthuizen, 2020), which all occurred in the new and unfamiliar university environment (Nyar, 2021). Not surprisingly, Moosa and Bekker (2022) found that first-year students in South Africa experienced anxiety due to the pandemic and its ramifications.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…For example, Bantjes et al (2022) found higher rates of non-fatal suicidal behaviour among first-year university students in South Africa. Stressors related to the first-year experience in the context of COVID-19 compromised the various aspects of South African first-year students' well-being including the physical, emotional, social and financial (Moosa & Bekker, 2022). Getting enough sleep, healthy eating, and exercising have been reported in assisting students with experiencing less stress and negative mental health challenges (Moses et al, 2016).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%